Undoing the Factory Model: A Practical Field Test in Blended Learning - Adam C. Holden (The Advocate, 2013)
Merely, introducing new technologies into the classroom does little to address the needs of students–while it might create a welcome instructional environment for them, it does not address the compelling “elephant in the room.” Being able to orchestrate a student-centered, technology-rich lesson requires much expertise on the part of the teacher and a system-wide universally acknowledged educational technology plan. This study examines the paradigm shift required of teachers and the practical reality of adopting a blended learning environment to meet the needs of a diverse school district.